Nursing care for Pregnant and Postpartum Women During the COVID-19 Pandemic - Araújo, Teresinha Oliveira Lima de; Bezerra, Maria Eduarda Lopes de Macedo; Silva, Daiane de Matos; de Souza Santos, Rutiele; Araújo, Taís da Silva; Santos, Ana Lara Martins dos; Cruz, Williane Pereira; Silva, Jhayne Gislayne Lavor da; de Souza Almeida Guedes, Thiemmy (Brazilian Journal of Science, 2022)
The nursing care provided or from prenatal to postpartum is extremely important to avoid possible health problems for both the fetus and the pregnant woman. Care related to the virtue of the coronavirus, benefits of assistance to assistance mainly with social isolation and public fear. Thus, this study aims to verify in the scientific literature the negative impacts that the pandemic has brought on nursing care for pregnant and postpartum women. This is an integrative literature review carried out in the LILACS, MEDLINE, BDENF and VHL databases, through the following DeCS: "Pregnancy; Postpartum period; COVID-19; Nursing Care"; combined with each other by the Boolean operator AND. The search did not take place in October 21 and 10 studies were selected for review. Nursing studies may have the need for nursing care that is of psychological quality, sufficiently capable of meeting the needs of pregnant women.